Analisis faktor-faktor yang mempengaruhi Tingkat Partisipasi Angkatan Kerja (TPAK) di Provinsi Jambi - Igo Septa Saputra; Zulfanetti Zulfanetti; Jaya Kusuma Edi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This research aim to: First, analyze the development of labor force participation rate, minimum wages, consumer price index and gross regional domestic product in Jambi Province. This study use time series data between 2000-2017 with data analysis method used namely quantitative descriptive analysis and Ordinary Least Square (OLS) method. Based on the result of data processing using the OLS method in multiple regression equations in 2000-2017 results were obtained. That the average development of the labor force participation rate, minimum wage, consumer price index and gross regional domestic product fluctuative from year to year. Based on processing data obtained results: (1) Consumer price index variable have a positive and not significant effect on labor force participation rate in Jambi Province; (2) The variable minimum wages and gross regional domestic product have a positive and significant effect on minimum wages in Jambi Province. Keywords: Labor Force Participation Rate, Minimum Wages, Consumer Price Indexand, and Gross Regional Domestic Product.